2006
DOI: 10.4319/lo.2006.51.6.2621
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary

Abstract: We used a three-dimensional physical-biological model consisting of a Eulerian circulation model and a Lagrangian particle-tracking model, which included vertical sinking and swimming, to explore zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary (SLETZ). To test the accuracy of the model, the results were temporally and spatially compared to a passive scalar released simultaneously in the circulation model and to field data for zebra mussel veligers. The model was then used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
(45 reference statements)
2
31
0
Order By: Relevance
“…These considerations, in addition to visual The passive accumulation of phytoplankton in the St. Lawrence River ETM requires further questioning. Simons et al (2006) calculated a residence time for free-floating particles such as algae of approximately 15 d in the ETM, which is in the same range of our observed 10-to 25-fold increase in peak chl a concentrations in the ETM compared to upstream concentrations. This indicates that the phytoplankton in the ETM achieves a relatively slow turnover rate of δ 34 S since the values for phytoplankton throughout the sampling zone are very close to those of the freshwater periphyton.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These considerations, in addition to visual The passive accumulation of phytoplankton in the St. Lawrence River ETM requires further questioning. Simons et al (2006) calculated a residence time for free-floating particles such as algae of approximately 15 d in the ETM, which is in the same range of our observed 10-to 25-fold increase in peak chl a concentrations in the ETM compared to upstream concentrations. This indicates that the phytoplankton in the ETM achieves a relatively slow turnover rate of δ 34 S since the values for phytoplankton throughout the sampling zone are very close to those of the freshwater periphyton.…”
Section: Discussionsupporting
confidence: 63%
“…towards the ETM). Moreover, Simons et al (2006) reported a residence time of 15 d for passive particles in the ETM (such as phytoplankton cells), due to the hydrodynamic entrapment zone described above. The combination of a large advection of phytoplankton cells upstream and a relatively long particle residence time may favor the retention of phytoplankton cells in the ETM.…”
Section: Introductionmentioning
confidence: 99%
“…The lower winter abundance and delayed spring increase are most likely due to higher advective losses during periods of high flow combined with sluggish development of the copepods at low winter temperatures. Advective losses due to high flow can overcome the ability of tidal vertical migration to hold copepods in place except in deep areas with enough of a salinity gradient to cause strong stratification (Simons et al, 2006;Kimmerer et al, 2014a).…”
Section: Abundance and Flow Responsesmentioning
confidence: 99%
“…Effectively, by changing vertical position at appropriate tidal phases, organisms, such as copepods or larval fish, can move large distances each tidal cycle or maintain a geographic position despite water movement. For example, using 3-D modeling, Simons et al (2006) showed how various zooplankton could maintain particular positions in the LSZ of the St. Lawrence Estuary (see also North et al 2008). Tracking individual "particles" with behavior moved by flow has also been used to assess connectivity of different regions in space, e.g., different coral reefs in the Caribbean (Cowen et al 2000) and regions of the California coast (Simons et al 2013).…”
Section: Using Models To Understand Fish Behavior and Movementmentioning
confidence: 99%
“…However, there is the substantial challenge of knowing the behavior to be used in the model. For example, depending on which of the bioenergetically possible swimming behaviors Mysid shrimp used in the St. Lawrence Estuary, Simons et al (2006) found that there could be either upstream migration from the LSZ to Montreal, maintenance of position in the LSZ, or downstream migration into the Atlantic Ocean. Nonetheless, as suggested by Banas et al (2009) in the context of modeling nutrient-phytoplankton dynamics in the Washington Shelf-Salish Sea region, this form of coupled modeling may also offer researchers the ability to invert observed data on the distribution of organisms to infer behavior.…”
Section: Using Models To Understand Fish Behavior and Movementmentioning
confidence: 99%